GEREJA SEBAGAI WADAH KONSTRUKSI KARAKTER TANGGUNG JAWAB BAGI GENERASI MUDA GEREJA MASA KINI - Karoma, Alfianus (Journal of Mandalika Literature, 2022)
The younger generation is an integral part of the church so it needs to be given attention and its character is formed and developed, especially the character of service responsibility. Not a few of the younger generation of the church are not involved in ministry because they feel neglected and not given a role so they stay away from church fellowship. The method used in this research is literature research with a descriptive qualitative approach to describe the church as a place for the reconstruction of the character of responsibility for today's young generation with Milles and Huberman's analytical theory. The research results show that the church and education are closely related, the church is a place for the reconstruction of the character of responsibility, the younger generation is an integral part of the church that needs to be served and empowered, and the church reconstructs the character of the younger generation through various productive and creative activities. This paper is expected to contribute thoughts and development for character education for community members, especially the younger generation in carrying out ministry in the congregation.